Protein of a thousand faces: The tumor-suppressive and oncogenic responses of p53 - Marques, Mayra A.; Andrade, Guilherme C. de; Silva, Jerson L.; de Oliveira, Guilherme A. P. (Frontiers in Molecular Biosciences, 2022)
The p53 protein is a pleiotropic regulator working as a tumor suppressor and as an oncogene. Depending on the cellular insult and the mutational status, p53 may trigger opposing activities such as cell death or survival, senescence and cell cycle arrest or proliferative signals, antioxidant or prooxidant activation, glycolysis, or oxidative phosphorylation, among others. By augmenting or repressing specific target genes or directly interacting with cellular partners, p53 accomplishes a particular set of activities. The mechanism in which p53 is activated depends on increased stability through post-translational modifications (PTMs) and the formation of higher-order structures (HOS). The intricate cell death and metabolic p53 response are reviewed in light of gaining stability via PTM and HOS formation in health and disease.